Modern algebra : an introduction - Durbin, John R. (New York : John Wiley and Sons, 2000)
Mappings and operations. Introduction to groups. Equivalence. Congruence. Divisibility. Groups. Group homomorphisms. Introduction to rings. The familiar number systems. Polynomials. Quotient rings. Field extensions. Polynimial equations. Geometric constructions. Application of permutation groups. Symmetry. Algebraic coding. Lattices and boolean algebras.
Keywords: Abstract of Algebra; Mathemetics; Algebra, Abstract